INOVASI KOMITE SEKOLAH DALAM MENGATASI TANTANGAN PENDIDIKAN DI ERA DIGITAL: STUDI KASUS DI BANGKALAN MADURA - AF, Habibur Rahman; Warisno, A; Siti, Patimah; Arafah, A Latief Arung (FIKRAH, 2024)
This article discusses the innovations carried out by the School Committee at Madrasah Aliyah Nurul Iman in facing the challenges of education in the digital era. Education in the digital era faces significant challenges that require innovation and adaptation fromvarious stakeholders, including school committees. This research aims to identify and analyze innovations carried out by the School Committee at Madrasah Aliyah Nurul Iman, located in Labang District, Bangkalan Regency, East Java Province, in facing the challenges of education in the digital era. The method used in this research is a case study with a qualitative approach. Data was collected through in-depth interviews, observations and document analysis with participants consisting of school committee members, teachers, students and parents. The results of the research show that the School Committee at Madrasah Aliyah Nurul Iman has carried out various innovations to improve the quality of education. These innovations include the use of information technology in the learning process, increasing teacher capacity through training and workshops, as well as collaboration with various external parties such as universities and technology companies. The implementation of information technology includes the use of e-learning platforms, learning applications, and hardware such as computers and projectors, which make learning more interactive and accessible to students.